Tuberculosis in the institutional environment - Sanger, John M.; MARCOM Group, Ltd. (Boothwyn, Pa.) (Boothwyn, Pa. : The MARCOM Group, Ltd., 1997)
This programs explains the history of Tuberculosis as a disease, epidemiology and symptomps of Tuberculosis, modes by which Tuberculosis is transmitted, and the details regarding the Tuberculosis
Title from title screen
Subtitle on presenter's guide: Training for the CDC tuberculosis prevention guidelines
Executive producer, Donald L. Leonard
Narration: Craig Butcher
Keywords: Centers for Disease Control and Prevention (U.S.).; Tuberculosis -- Prevention; Safety education; Industrial safety